Digital technologies: a paradox between exclusion and social protection (Emancipação, 2026)
The article critically analyzes digitalization in Brazil’s social security system, particularly in social assistance, and its  effects on vulnerable populations. Using an intersectional  and decolonial approach, it discusses how technologies can expand access but also deepen inequalities when detachedfrom territorial realities. Based on a comparison between Auxílio Brasil and the Cadastro Único, the study examines the limits and potential of digital transformation in the SUAS for guaranteeing rights. The action-research methodology included document analysis, open data, and socioterritorial assessment. The findings show that digital  exclusion reinforces historical inequalities, while qualified data use can strengthen democratic processes when guided by social justice and participation. In this context, the  Cadastro Único emerges as a strategic tool for promoting equity in SUAS socioterritorial management. i
Keywords: Digital Government. Social Assistance. Cadastro Único